(untitled) (Brazilian Journal of Radiation Sciences, 2021)
The use of nuclear energy, as well as all human activity, generates wastes and these need to receive suitable treatments so that they don’t expose a risk to the public and the environment. Currently there is a project in Brazil whose objective is the implementation of a national repository for the final storage of low and intermediate level waste. The disposal of the radioactive waste is based on the concept of multiple barriers, in which packed wastes are conditioned in concrete containers, which are then placed in modules, which are closed and covered by natural materials. In this work, Steel Fiber Reinforced Concrete (SFRC) was studied as a substitute for the concrete with conventional steel reinforcement in the production of containers. Compressive and tensile strength tests were performed, as well as characterization and evaluation of steel fibers. 48 specimens of concrete were prepared with two types of fibers (A and C) and tested. The best results were obtained with the addition of 1.5% vol. of type A fibers. Through the carbon and sulfur quantification test it was possible to conclude the steel used in the fibers’ manufacture was low carbon. It was also possible to verify, using the folding test, the material used served the parameters of quality. This research project was supported by the Centro de Desenvolvimento da Tecnologia Nuclear (CDTN), the Comissão Nacional de Energia Nuclear (CNEN) and the Fundação de Amparo à Pesquisa do Estado de Minas Gerais (FAPEMIG).